The use of ESL textbooks and students’ performance in speaking: a case study of some secondary schools in Ringim LGA Jigawa state (British Journal of Multidisciplinary and Advanced Studies, 2024)
The role of English as a Second Language (ESL) textbooks in enhancing students' speaking abilities is a critical area of study, especially in regions where English is not the primary language. This research examines the influence of ESL textbooks on the speaking performance of secondary school students in Jigawa State, Nigeria. Adopting a qualitative research design, the study involved detailed interviews with teachers and focus group discussions with students from six secondary schools In Ringim local government of Jigawa state. The findings reveal that while ESL textbooks contribute to students' speaking development, the effectiveness varies significantly based on the alignment of textbook content with the local context and students' needs. The study concludes by recommending the integration of culturally relevant materials and interactive speaking exercises in ESL textbooks to better support students' oral communication skills.